Financial Reporting by Private Companies: Analysis and Diagnosis. (Book Review). - Stone, Mary S.; Hendrickson, Harvey S. (The Accounting Review, 1985)
Reviews the book "Financial Reporting by Private Companies: Analysis and Diagnosis," by A. Rashad Abdel-Khalik.